Thai university students’ self-regulated learning in an online learning environment - Budsaba Kanoksilapatham, (Penerbit Universiti Kebangsaan Malaysia, 2023)
Language learners’ achievement is influenced by a variety of psychological factors, including attention, self confidence, and motivation. In addition to the list, self-regulated learning (SRL) is another essential psychological component of learning, as evidenced by research on learning and performance. Meanwhile, rapid changes in current conditions induced by COVID-19 have prompted a shift from traditional face-to-face to online learning. In this learning environment, learners and instructors are physically apart, and thus very little is known about how their learning is navigated. To better understand how learners manage learning, this study examines Thai university students’ SRL application while taking an English course totally delivered online. Based on the administration of the 24-item Online Self-regulated Learning Questionnaire (OSLQ) at the end of the course, 75 out of the 84 students completed the questionnaire. Data analysis exhibited quite a high level of goal setting (GS) and environmental structuring (ES); however, they appeared to utilise a relatively lower level of task strategies (TS) and time management (TM). Overall, the findings underline the importance of instiling SRL in students and suggest that SRL may vary depending on academic contexts. The results contribute to our understanding of the association between learning environments and SRL, as well as providing practical pedagogical implications to enhance students’ success.